Flow cytometric analysis of cerebrospinal fluid improves detection of leukaemic blasts in infants with acute lymphoblastic leukaemia. (15th August 2021) - Thastrup, Maria; Marquart, Hanne Vibeke; Levinsen, Mette; Modvig, Signe; Abrahamsson, Jonas; Albertsen, Birgitte Klug; Frost, Britt‐Marie; Harila‐Saari, Arja; Pesola, Jouni; Ulvmoen, Aina; Wojcik, Dorota Malgorzata; Taskinen, Mervi; et al.
Summary: Infants with acute lymphoblastic leukaemia (ALL) have a high frequency of central nervous system (CNS) involvement. Flow cytometric analysis of cerebrospinal fluid (CSF) was recently demonstrated to be a sensitive method for detecting CNS involvement in childhood ALL. In the present study, CSF from 14 infants was collected at routine lumbar punctures and analysed by multicolour flow cytometry. At initial diagnosis, leukaemic blasts were detected in CSF by flow cytometry in 11 patients (78·6%) compared to seven patients (50%) by cytospin. Larger studies are needed to determine if CSF flow cytometry has prognostic value in infant ALL.